XANES measurements of sulfur chemistry during asphalt oxidation. (15th December 2015) - Greenfield, Michael L.; Byrne, Michael; Mitra-Kirtley, Sudipa; Kercher, Eric M.; Bolin, Trudy B.; Wu, Tianpin; Craddock, Paul R.; Bake, Kyle D.; Pomerantz, Andrew E.
Graphical abstract: Highlights: Sulfur chemical speciation in a warm-mix asphalt was measured by sulfur K-edge XANES. Changes in sulfur speciation as a consequence of RTFO and PAV aging were quantified. More sulfide is unoxidized than converted to sulfoxide under RTFO or PAV conditions. Thiophene is the dominant sulfur form regardless of extent of aging. Abstract: Sulfur K-edge X-ray absorption near-edge structure (XANES) spectroscopy is used to measure how the speciation of sulfur compounds evolves within a warm-mix asphalt as a consequence of the Rolling Thin-Film Oven (RTFO) and Pressure Aging Vessel (PAV) oxidative aging procedures. Identifying the types of sulfur compounds present is important for quantifying the growth in polar sulfur-containing species that can alter the asphalt's mechanical properties over time. Elemental analysis indicates that the sulfur content of the asphalt holds constant at 5 wt% during aging. XANES analysis indicates that thiophenic sulfur compounds are most prevalent (62%), followed by sulfide and elemental sulfur compounds. RTFO and PAV aging cause smaller and larger shifts, respectively, from sulfide to sulfoxide. The amount of unreacted sulfide remains larger than the amount of sulfoxide, even with PAV aging. The XANES spectra lack features that would be expected if engine oil additives indicative of recycled engine oil bottoms were present. The results indicate the importance of including thiophene, sulfide, and sulfoxide chemistries within molecular asphalt models.